Streaming Science #3: Using Scientist Online Electronic Field Trips for Engagement with Your Target Audience - Jamie Loizzo; Caroline Barnett; Christine Krebs; Gabriel Spandau (EDIS, 2022)
This is the third publication in the Streaming Science EDIS series focused on how to use mobile hardware and software for engagement with your target audience. This new 6-page publication of the UF/IFAS Department of Agricultural Education and Communication focuses on a model called Scientist Online for live webcast electronic field trips (EFTs). Through Scientist Online EFTs, Streaming Science connects university scientists and Extension professionals with PK-12 students around the world for small-scale presentations, demonstrations, and discussions. Written by Jamie Loizzo, Caroline Barnett, Christine Krebs, and Gabriel Spandau. https://edis.ifas.ufl.edu/wc424